Tautomers of a Fluorescent G Surrogate and Their Distinct Photophysics Provide Additional Information Channels - Sholokh, Marianna; Improta, Roberto; Mori, Mattia; Sharma, Rajhans; Kenfack, Cyril; Shin, Dongwon; Voltz, Karine; Stote, Roland H.; Zaporozhets, Olga A.; Botta, Maurizio; Tor, Yitzhak; Mély, Yves (Angewandte Chemie International Edition, 2016)
Thienoguanosine (thG) is an isomorphic nucleoside analogue acting as a faithful fluorescent substitute of G, with respectable quantum yield in oligonucleotides. Photophysical analysis of thG reveals the existence of two ground‐state tautomers with significantly shifted absorption and emission wavelengths, and high quantum yield in buffer. Using (TD)‐DFT calculations, the tautomers were identified as the H1 and H3 keto‐amino tautomers. When incorporated into the loop of (−)PBS, the (−)DNA copy of the HIV‐1 primer binding site, both tautomers are observed and show differential sensitivity to protein binding. The red‐shifted H1 tautomer is strongly favored in matched (−)/(+)PBS duplexes, while the relative emission of the H3 tautomer can be used to detect single nucleotide polymorphisms. These tautomers and their distinct environmental sensitivity provide unprecedented information channels for analyzing G residues in oligonucleotides and their complexes. Channel surfing: A faithful isomorphic guanosine analogue, thG, exists in two emissive ground‐state tautomers. Both forms are present in single‐stranded oligonucleotides and show sensitivity to protein binding, while only the thG‐H1 tautomer is favorable in duplexes. These tautomers and their distinct photophysics are shown to be highly valuable for analyzing G residues in oligonucleotides and their complexes. (d)Rib=2′‐deoxy‐d‐ribose.